2015
DOI: 10.1002/cncr.29356
|View full text |Cite
|
Sign up to set email alerts
|

Association of surgeon volume and hospital volume with the outcome of patients receiving definitive surgery for colorectal cancer: A nationwide population‐based study

Abstract: BACKGROUND:Patients with colorectal cancer (CRC) who undergo cancer surgeries with higher-volume providers may have better outcomes. The current debate focuses on whether it is hospital volume or surgeon volume that matters more. METHODS: The authors conducted a nationwide population-based study in Taiwan that enrolled all patients who underwent definitive surgery for newly diagnosed CRC between 2005 and 2011. All patients were divided into 4 quartiles according to hospital and surgeon volume. The main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 33 publications
4
59
1
4
Order By: Relevance
“…This is likely because the inclusion criteria for the current study were limited to those patients who had received neoadjuvant chemoradiotherapy and therefore were more likely to have been treated at high‐volume centers. Nevertheless, the results of the current study add to the mounting literature of volume effects on guideline adherence and outcomes . Although the hospital‐level factors included in our model were associated with the increased administration of adjuvant therapy, they do not explain a large percentage of the hospital variation that was observed in the current model.…”
Section: Discussionmentioning
confidence: 47%
“…This is likely because the inclusion criteria for the current study were limited to those patients who had received neoadjuvant chemoradiotherapy and therefore were more likely to have been treated at high‐volume centers. Nevertheless, the results of the current study add to the mounting literature of volume effects on guideline adherence and outcomes . Although the hospital‐level factors included in our model were associated with the increased administration of adjuvant therapy, they do not explain a large percentage of the hospital variation that was observed in the current model.…”
Section: Discussionmentioning
confidence: 47%
“…Numerous studies have reported that hospital volume as well as surgeon volume are independent predictors of longterm outcomes in surgically treated cancer patients (1)(2)(3)(4)(5). This association was attributed to the hospital and surgeon's experience which yielded improved rates of achieving negative margins (6)(7)(8) and higher rates of dissecting involved lymph nodes (6,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Research into quality improvement in surgery has focused on the effect of surgeon and hospital volume on outcomes 15,16 . Spillane et al 6,8 demonstrated a higher lnrr for surgeons at the high-volume Sydney Melanoma Unit than for other Australian surgeons.…”
Section: Discussionmentioning
confidence: 99%